(3SYQ UQa GdOjfGQ GdLRGFQj Hjf hGbYjI GdShb h GdJYOjd Gdgjcdj (B:s (3ebGQHI JhbYjI h GMJjGWjI (B/s - (3YRj, GdGNVQ CHh YdGAs ((3GdLRGFQ(B: s (3OGQ GdNdOhfjI(B, s, 2010)
(3eYQaI GdbOQGJ GdcHjQI ddEbJUGO GdLRGFQj Ydi GdeSJhi Gdcdj hGdLRFj (B-(3EeGWI GddKGe Yf GdUQa GdehGRj hJHfj GbJUGO GdShb ef hGbY GdVHW GdOGNdj GdPGJj hcPG JhLjgGJ GdUfOhb GdfbOj GdOhdj(B- (3eYQaI GdhVY GdEbJUGOj Gdcdj ddLRGFQ YHQ GdOhQGJ GdGbJUGOjI(B- (3GdSjGSI GdfbOjI hGTcGdjI GdYedI aj GdLRGFQ(B- (3GTcGdjI ejRGf GdeOahYGJ GdLRGFQj(B- (3GdGSS hGdQhGaO GdJYOjdjI dGfYGT GdOjfGQ GdLRGFQj(B.s
(3eQGLY U(B.106 (3; edGMb h GTcGd U(B.96s
Keywords: (3GdCShGb GdeGdjIs; (3GdEbJUGO(B- (3GdLRGFQjs; (3SYQ GdUQas